The Cross in the Visual Culture of Late Antique Egypt - Spalding-Stracey, Gillian, (Texts and Studies in Eastern Christianity ;, 2020)
In The Cross in the Visual Culture of Late Antique Egypt Gillian Spalding-Stracey brings the design of crosses in monastic and ecclesiastical settings to the fore. Visual representations of the Holy Cross are often so ubiquitous in Christian art that they are often overlooked as artistic devices themselves. This volume offers an exploration of the variety of designs and associated imagery by which the Cross was expressed across the Egyptian landscape in late antiquity. A survey of locations and images leads to an analysis of artistic influences, possible symbolism, variance across time and place and the contextual use of the motif. Gillian Spalding-Stracey provides the reader with an art-historical perspective of the socio-cultural situation in Egypt at the time.